The Legal Impact of Free Nutritious Food Programs Due to Mass Poisoning in East Java Region Reviewed from a Human Rights Perspective - Fitri Ayu Raamdhani; Vieta Imelda Cornelis; Sri Astutik; Nur Handayati (Green Publisher Indonesia, 2025)
This study uses a normative legal research method with a conceptual approach (Conceptual Approach) and a case approach (Case Approach). The main data sources are primary legal materials (the 1945 Constitution of the Republic of Indonesia, Law No. 39 of 1999 concerning Human Rights, regulations related to food safety) and secondary legal materials (scientific journals, proceedings, and news reports related to the MBG poisoning incident in East Java). The mass poisoning incident in the MBG program in East Java indicates a violation of the state's obligation to guarantee human rights. The state, through the program implementing apparatus, was negligent in applying the principle of due diligence. The results of the study indicate a lack of substantive norms related to minimum hygiene standards (SLHS/HACCP) and accountability in the food supply and supervision chain. The legal impacts that arise include criminal, civil, and administrative liability for catering providers and related officials who are proven negligent, as well as violations of Article 28H paragraph (1) of the 1945 Constitution concerning the right to a prosperous life physically and mentally. Systemic reforms in the governance of the MBG program, strengthening of food safety regulations, and transparent legal accountability mechanisms are needed to restore victims' rights and prevent recurrence of incidents.